Students’ Attitude Toward Science and Interest in STEM Careers - Dumapias, Ronald Camongol (Future Science / FSH-PH Publications, 2025)
Science, technology, engineering, and mathematics (STEM) are considered important areas in today’s society. However, it can be observed that fewer STEM graduates enter the workforce and contribute to the nation’s progress. This can be attributed to students' lack of interest in pursuing STEM careers. One factor influencing the interest in STEM is the students' attitude toward their science subjects. The main purpose of this study is to examine the relationship between attitudes toward science and students’ interest in careers related to STEM. Further, this research investigated which aspect of attitudes toward science can significantly predict the level of interest in pursuing STEM. An online survey was conducted on 243 grade 9 students of Pasig City Science High School to gather data regarding their attitudes toward science and their interest in STEM careers. The survey results were analyzed using the Pearson correlation coefficient and multiple regression analysis. Results revealed a moderate positive relationship between the students’ attitude toward science and their interest in STEM careers (r = .54, p < .001). Meanwhile, multiple regression analysis disclosed that the aspects of attitudes toward science, namely the students’ interest in science, their value for science, and their confidence in science, can predict their interest in STEM (F(3,239)=85.43, p < .001, R2 = .52), explaining 52% of the variance. However, among these aspects, the students’ value for science is the most predictive and was the only significant predictor (β = .65, p < .001).